Klasifikasi Nilai Pengurus Teladan Pondok Pesantren Nurul Jadid Menggunakan Metode K-Nearest Neighbor (KNN) - Jasri, Moh.; Ghozali, Achmad Fais; Sukron (SMARTICS Journal, 2024)
In determining exemplary administrators, there are several assessment criteria that have been designed by looking at all the tasks and programs carried out. This is done to encourage administrators to be more enthusiastic in their service at Islamic boarding schools. Apart from that, this program is also an evaluation for management who need to follow up on their negligence in all duties and responsibilities. From the research carried out, there is a problem, namely in determining exemplary administrators, currently at the Nurul Jadid Islamic Boarding School it is only based on observations of regional heads and regional heads, and does not pay attention to assessment criteria and indicators in the form of professionalism, personality and social issues. Therefore, a decision support system implemented in web form is very necessary to solve the problems that occur. The programming language used is PHP (Hypertext Preprocessor) using the CodeIgniter framework. The hope is that the resulting website can help regional and regional heads make the right decisions for exemplary organizers. K-Nearest Neighbor (KNN) is the method used for classification in this research. The KNN algorithm uses the k value to determine the number of nearest neighbors whose status will be calculated. The data used is 348 lines of management assessment data for 2021-2023. Optimizing the k value using k-fold cross validation produces the highest level of accuracy, namely 97.70% with a value of k = 4 and training data of 75% of the total previous assessment data.